Electrical Engineering and Applied Computing - Ao, Sio-Iong; Gelman, Len (Lecture Notes in Electrical Engineering, 2011)
This book includes fifty-five chapters, revised and extended from research articles originally presented at the World Congress on Engineering 2010. Topics covered include Control Engineering, Network Management, Wireless Networks, Biotechnology, Signal Processing, Computational Intelligence, Computational Statistics, Internet Computing, High Performance Computing, and industrial applications. The book offers the state of the art of tremendous advances in electrical engineering and applied computing and also serves as an excellent reference work for researchers and graduate students working on electrical engineering and applied computing.